The Job Satisfaction of Expatriate American Managers: - Miller, Edwin L. (Journal of International Business Studies, 1975)
This paper presents the results of a study concerned with the need satisfactions of Americans who are assigned to international managerial positions. The results of the study indicate that regional location and prior international work experience influence the job satisfaction of overseas managers. It is suggested that jobs in different parts of the world may be viewed differently because of previous international work experience, career aspiration and control exerted by the parent organization.